Analisis Rasio Keuangan untuk Bisnis yang Berkelanjutan Perusahaan - Destari, Yuri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to identify the ability of companies in profit-seeking and provide a measure of the level of effectiveness of company management. This analysis is done by comparing the various components of the company's financial statements for 2016, 2017 and 2018 using the type of quantitative research and descriptive analysis. The Gross Profit Margin rate from 2016 to 2018 was 32.07%, 35.93% and 37.30%. While the Net Profit margin for 2016 upto 2018 was 4.67%, 5.41% and 5.39%. The Return On Equity rate during 2016 reached 11.96%, 12.89% and 11.97%. The return on assets rate decreased during 2016 to 5.89%, 5.44% and 4.25%. The results of the analysis show a decrease from year to year. The average figure of the profitability ratio is still below the standard can be said to be poor. Therefore, the management of the company must be more creative and innovative in order to increase revenue so that it can raise the profitability ratio of KAEF.